A facile three-component route to powerful 5-aryldeazaalloxazine photocatalysts - Weisheitelová, Ivana; Cibulka, Radek; Sikorski, Marek; Pavlovska, Tetiana (Beilstein Journal of Organic Chemistry, 2024)
Functionalized 5-aryldeazaalloxazines have been successfully synthesised through a one-pot, three-component reaction involving N,N-dimethylbarbituric acid, an aromatic aldehyde and aniline. By utilizing readily available reagents, this approach opens up the opportunity for the efficient formation of a variety of 5-aryldeazaalloxazines bearing electron-donating or halogen groups. This practical method is characterised by atom economy and offers a direct route to the introduction of an aryl moiety into the C(5)-position of deazaalloxazines, thereby generating novel catalysts for photoredox catalysis without the need for subsequent purification. Thus, it significantly improves existing approaches.
Keywords: catalysis; deazaalloxazine; flavin; multicomponent approach; one-pot reaction